Unique Presentation and Management Approach of Pleural Solitary Fibrous Tumor - Tarek Aridi; Ayman Tawil; Mohamad Hashem; Joe Khoury; Roy A. Raad; Pierre Youssef (Case Reports in Surgery)
Solitary fibrous tumor (SFT) of the pleura is an uncommon tumor that is often discovered incidentally on a routine chest X-ray. We report a case of a young female with a large, sessile, hypervascularized SFT of the pleura presenting with cardiopulmonary shock to a rural hospital with limited therapeutic interventions. We propose, in this case report, a unique multidisciplinary approach for the management of such a critical patient and the safe resection of the tumor.